AN APPLICATION OF THEORY REASONED ACTION TO EXAMINE FACTORS EXPLAINING RESIDENTS’ SUPPORT FOR COMMUNITY-BASED TOURISM - Untong, Akarapong (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2022)
This article aims to develop and examine the consistency of a causal relationship model of the factors explaining the resident’s support for community-based tourism in Koh Yao Noi community, Phang Nga Province. The model contains seven latent variables, which measured from 20 observable variables. The sample is the 246 local people living in Koh Yao Noi, Phang Nga Province. The questionnaire was used as a research tool while applying the structural equation model to analyze the data. The results from the study found that the role toward community-based tourism was the factor that had the highest total effect factor on community-based tourism support of local people, followed by the perception of community-based tourism and the perception of the benefits from community-based tourism, respectively. On the other hand, the perceived negative effects of community tourism had the lowest total effect on the local residents’ support for community-based tourism. Therefore, to encourage local people to support community-based tourism, stakeholders should pay more attention to increase the role of local residents in the operation of community-based tourism, especially providing opportunities for local people to support various activities related to community-based tourism. In the meanwhile, the information should be provided to educate local residents about community-based tourism and the benefits arising from community-based tourism.